DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN HEMODIALISIS DI RSUD Dr. R. KOESMA TUBAN - Yasin Wahyurianto; Teresia Retna Puspita Dewi; Roudlotul Jannah (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Patients with chronic kidney disease undergoing hemodialysis undergo long-term therapy, which significantly impacts their quality of life. The quality of life of patients with chronic kidney disease undergoing hemodialysis requires further investigation, as quality of life issues are of utmost importance in patient-centered healthcare. An initial survey conducted in May 2024 in the Hemodialysis Unit of Dr. R Koesma General Hospital in Tuban found that 29 (22%) patients did not have family members accompanying them. Family support for patients with chronic kidney disease undergoing hemodialysis is an important support system. The aim of this study was to determine the relationship between family support and the quality of life of patients with chronic kidney disease undergoing hemodialysis. The study design was an analytical correlational study. The sample consisted of 70 patients, selected using total sampling. The instruments used were the WHOQOL and a family support questionnaire developed by Marbun (2017). Data were analyzed using the Spearman Rank test. The results showed that nearly half of the chronic kidney disease patients undergoing hemodialysis were aged 46–55 years, most were male, nearly half had a high school education level, most were unemployed, and nearly half had been undergoing hemodialysis for 1–3 years. All chronic kidney disease patients undergoing hemodialysis received good family support and had very good quality of life. There was no significant relationship between family support and the quality of life of CKD patients undergoing hemodialysis (p = 0.483). In conclusion, the quality of life of CKD patients is more influenced by factors such as physical health status, disease severity, adherence to therapy, or access to health services than by family support. Based on the results of this study, further research is needed on families to improve support for CKD patients who are classified as having chronic diseases.